2022
DOI: 10.1097/mat.0000000000001866
|View full text |Cite
|
Sign up to set email alerts
|

Pneumoperitoneum and Acute Kidney Injury—An Integrative Clinical Concept Review

Abstract: An increased intraabdominal pressure, particularly when occurring during periods of hemodynamic instability or fluid overload, is regarded as a major contributor to acute kidney injury (AKI) in intensive care units. During abdominal laparoscopic procedures, intraoperative insufflation pressures up to 15 mmHg are applied, to enable visualization and surgical manipulation but with the potential to compromise net renal perfusion. Despite the widely acknowledged renal arterial autoregulation, net arterial perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 132 publications
(257 reference statements)
0
3
0
Order By: Relevance
“…However, it has been reported that these deteriorations are not evident in the clinic when the pressure is 15 mmHg or less [ 16 ]. As long as the intra-abdominal pressure does not exceed 15 mmHg during laparoscopic procedures, the decrease in cardiac output is minimal and does not affect the clinical outcome in healthy subjects [ 17 ]. As in these studies, surgical procedures in our study were performed with insufflation pressures of 15 mmHg and below.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that these deteriorations are not evident in the clinic when the pressure is 15 mmHg or less [ 16 ]. As long as the intra-abdominal pressure does not exceed 15 mmHg during laparoscopic procedures, the decrease in cardiac output is minimal and does not affect the clinical outcome in healthy subjects [ 17 ]. As in these studies, surgical procedures in our study were performed with insufflation pressures of 15 mmHg and below.…”
Section: Discussionmentioning
confidence: 99%
“…Kopitko et al. conducted a comprehensive review on the impact of elevated IAP on the kidneys, encompassing aspects such as blood perfusion, and humoral factors, and comparing open and laparoscopic approaches, anesthesia and sedation [ 25 , 26 ]. Nevertheless, this perspective seems not to have garnered sufficient attention among surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…But it is likely to be caused by direct compression of Pnp on renal parenchyma and vasculature, leading to increased vascular resistance, venous and lymphatic congestion, and decreased renal blood flow. [ 2 , 3 ] Renal autoregulation results in the stimulation of the renin–angiotensin–aldosterone system (RAAS), with increasing renin release and subsequent aldosterone secretion. Second, neuroendocrine responses result in the excretion of the anti-diuretic hormone.…”
Section: Introductionmentioning
confidence: 99%